Spatial development of Bajo tribal residence in Wuring Village Maumere City - Antariksa; Ambrosius A. K. S. Gobang; Agung Murti Nugroho (ARTEKS : Jurnal Teknik Arsitektur, 2017)
The spatial condition of the Bajo Tribe at Wuring village in Maumere Town is seen in the characteristics to residential community as early village of Muslim civilization and became the center of spreading out Islam in Sikka Regency. The historical background is as a review in exploring the formation’s community dwelling and geographical, social, cultural and economic aspects of the local community. This approach in research using phenomenology method with qualitative descriptive and naturalistic analysis that is describing and interpreting cultural record of Bajo Tribe in the form of description of history, map document, or artefact which in the form of physical resident of Bajo tribe society. The purpose of this study is to examine the spatial development that is formed in the form of spatial system to residential and the aspects underlying the spatial establishment of Bajo Tribe in Wuring village area as an effort to understand the initial condition until the formation of the present kampung hamlet. The result of this research gives general ilustration about occupancy spatial system including space organization, space orientation and space of hierarchy in micro scope of residence in the form of ma'bunda-ma'buli concept. On the other hand, it is also on environmental messo like form of spatial development shelter in the form of grow stage and diaruma stage because of the non-physical aspect underlined spatial formulation of dwellings to the area of ​​Wuring village.